PENGARUH PENDIDIKAN TINGGI AKUNTANSI TERHADAP KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL PADA MAHASISWA AKUNTANSI UNIVERSITAS ISLAM MALANG DAN UNIVERSITAS TRUNOJOYO MADURA 2014-2016 - Lutfia Ermayani; Nur Diana (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe purpose of this study is to examine accountant education to emotionalintelligent and emotional spiritual to student college accountancy. Techniquesampling in the study using random sampling technique. This study using studentcollege accountancy generation 2014-2016 as a sample. Data in this study usingprimary data and this research was located in University of Islamic Malang andUniversity of Trunojoyo. The character of this study is explanatory research.Analysis to examine the correlation of the variables using the quality test and thenormality test with the hypotheses which the t test and the correlation test. Theresult shows the modeling of instructor teaching and learning environmentinfluenced significantly to emotional spiritual to student college accountancy.Keyword : The modeling of instructor teaching, learning environment, emotionalintelligent, emotional spiritual.